Fear of childbirth among pregnant mothers at Hospital USM, Kelantan - Yi, Ong Yi (Universiti Sains Malaysia, 2023)
Fear of childbirth (FOC) can severely impact a woman's mental health throughout pregnancy and her birth experience. However, the extent to which childbirth alters the trajectory of FOC is under researched in Malaysia. This study aimed to determine the FOC and risk factors in a cohort of birthing mothers at a tertiary teaching hospital in northeast peninsular Malaysia. A cross-sectional study was conducted among 243 birthing mothers recruited via a purposive sampling approach from February 2023 to March 2023. The Childbirth Fear Questionnaire (CFQ) and socio-demographic data were used to collect data, and a p-value < 0.05 was considered statistically significant. The mean age of the participants was 31.23 years (SD = 4.980), and the mean gestational age at enrolment was 33.51 weeks (SD = 5.967). Forty-nine (20.2%) participants reported low to mild FOC. The mean FOC score was 2.34 (SD = 0.564), and 38.3% and 11.1% reported moderate to severe FOC, respectively. Pearson's chi-square test showed statistical significance in the age group with FOC (p = 0.044), while Fisher's test revealed that FOC interference was significantly associated with age (p = 0.008) and parity (p = 0.019). Almost half of the birthing mothers were found to be moderate to severe FOC, respectively, and associated with age. In addition, age and parity were identified as associated with FOC interference. Therefore, tailored education and interventions are needed from healthcare policymakers and professionals to decrease childbirth fear and its mental health repercussions of mothers.